2006
DOI: 10.1007/s00213-006-0429-9
|View full text |Cite
|
Sign up to set email alerts
|

The early time course of smoking withdrawal effects

Abstract: These findings provide the first evidence of the early time course of smoking withdrawal symptoms, although further research is needed to distinguish withdrawal from drug offset effects. Implications for understanding the maintenance of daily smoking and for the treatment of tobacco dependence are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
190
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 98 publications
14
190
1
Order By: Relevance
“…Procedures for assessing early withdrawal effects followed those of an earlier study (Hendricks et al, 2006). Participants who met inclusion criteria during a telephone interview were scheduled for individual appointments at an inpatient research unit located at the San Francisco General Hospital between noon and 9:00 p.m. and were instructed to smoke as usual before their appointment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures for assessing early withdrawal effects followed those of an earlier study (Hendricks et al, 2006). Participants who met inclusion criteria during a telephone interview were scheduled for individual appointments at an inpatient research unit located at the San Francisco General Hospital between noon and 9:00 p.m. and were instructed to smoke as usual before their appointment.…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawal measures were those that demonstrated sensitivity to early smoking abstinence in a prior study (Hendricks et al, 2006). The order of administration at each of the nine early withdrawal assessments was as follows.…”
Section: Early Withdrawal Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since smokers shifted smoking from public to private places, non-smokers, and particularly young children, experienced higher exposure to secondhand smoke. Moreover, restricted opportunities for smoking may also negatively affect smokers because earliest smoking withdrawal symptoms occur within 30 minutes of abstinence (Hendricks et al 2006). In this context, Origo and Lucifora (2010) provide empirical evidence for increased levels of mental distress among smokers due to bans in European workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors contribute to the development and maintenance of nicotine addiction, and these processes have been investigated in both human populations and animal models to better understand underlying mechanisms. Cessation of chronic nicotine produces withdrawal symptoms in both animals (Grabus et al 2005;Malin et al 1992) and humans (Hughes 2007;Hendricks et al 2006), and avoidance of withdrawal symptoms is one factor that contributes to the maintenance of smoking and relapse during quit attempts. Conversely, studies have also shown that the severity and duration of nicotine withdrawal symptoms strongly predict relapse (Piasecki et al 1998(Piasecki et al , 2000.…”
mentioning
confidence: 99%